Id, Ego, and Superego in The Catcher in the Rye: A Psychoanalytic Literary Analysis - Suardi; Dyah Ambar Wuryandari; Wawan Wurjantoro (Lingua : Journal of Linguistics and Language, 2026)
Psychoanalytic approaches play an important role in literary criticism for examining the psychological complexity of characters. However, many studies remain general and do not explicitly analyze Freud’s structural model of personality within specific literary texts. This study aims to analyze the representation of the id, ego, and superego in The Catcher in the Rye by J.D. Salinger and to examine how their interaction shapes the development of the main character. This research employs a qualitative method using psychoanalytic literary analysis through close reading and thematic analysis. The data consist of selected textual units from the novel, including dialogue, narrative descriptions, and internal monologues that reflect the psychological conflicts of the protagonist, Holden Caulfield. The findings show that the id is represented through impulsive emotional reactions such as anger, alienation, and rejection of social norms, which initiate narrative tension. The ego appears in reflective moments where Holden evaluates his actions and attempts to negotiate between his desires and reality. Meanwhile, the superego is expressed through feelings of guilt, moral confusion, and concern for innocence, particularly in his interactions with his younger sister. These interactions contribute to the psychological development of the protagonist throughout the narrative. This study contributes to literary criticism by providing a text-specific psychoanalytic analysis and demonstrating how Freud’s structural model can be applied to interpret psychological conflict within a contemporary literary work.